A Comparative Study on the Homeroom Teachers’ Perception of the School guidance in Korea and Finland - Kim, Yoojin (fi=Turun yliopisto|en=University of Turku|, 2017)
This study has four major purposes. First, it compares school guidance of homeroom teachers in Korea and Finland, in order to understand the reality of education, based on the teachers’ perceptions. Secondly, it also considers the topic within its historical, social, and cultural backgrounds, from a critical standpoint. Thirdly, it investigates the direction of the improvement of school guidance, based on the analysis of similarities and differences between Korea and Finland, with regards to the meaning, practice, and environmental factors of the school guidance. Lastly, the influential factors surrounding the school guidance are noted by analysing empirical data from a microscopic approach, and extending the understanding of it into a social context. As for the methods, it employs thematic analysis approach through 10 homeroom teacher interviews in the lower secondary schools. As a result, firstly, the teachers in both countries assumed similarly, that the role of the teacher was not only to teach the subject, but also to care about every aspects of the students’ development in their school life. In addition, they accepted the fact that school guidance became more significant. However, the school guidance became the top priority for the Korean teachers, while teaching subject is the main task for the Finnish teachers. Secondly, the homeroom teachers in both countries hoped to have a better working environment, to perform school guidance concerning education budget for the resources of school guidance, tight curriculum, and increasing the teachers’ tasks. Thirdly, the school guidance in Korea seemed to be influenced by social expectation and government demand, whereas, the Finnish teachers considered school guidance in more aspects of adjustment and academic motivation, rather than resolving the social problems. Fourthly, the Korean teachers perceived that the trust and respect from the society and home became weakened, also expressing doubts about the educational policies and the attitude of the government with regards to school guidance. On the other hand, the Finnish teachers believed that they were trusted and respected by the society. However, blurred lines in the roles and accountability between the homeroom teachers, home, and the society were also controversial among the teachers in both countries. To sum up, Finland needs to ameliorate the system and conditions for school guidance of the homeroom teachers. The consensus on the role and tasks of Finnish homeroom teachers for school guidance seem to be also necessary. Meanwhile, Korea should improve the social system and social consciousness of the teacher, school guidance, and schooling, preceding the reform of the education system or conditions.